Dynamic Changes of Ocular Surface in First-Time Contact Lens Wearers and the Effective Factors of Contact Lens Discomfort - Xu, Yangyang; Xu, Zhiqiang; Shu, Xupeng; Liu, Qiaoli; Wang, Yuzhou; Xia, Jiahui; Li, Yong; Qu, Jia; Hu, Liang (Frontiers in Medicine, 2022)
Purpose: To investigate the dynamic changes of ocular surface indicators in first-time contact lens (CL) wearers, and to reveal the most influential factors in contact lens discomfort (CLD). Methods: Twenty-six healthy non-CL wearers (26 eyes) were recruited and fitted with monthly disposable hydrogel CLs. Each subject underwent a full ocular surface evaluation, including Efron grading, tear film break-up time, Schirmer's I test, corneal dendritic cells (DCs) imaging by in vivo confocal microscopy, and conjunctival microvasculature evaluation by functional slit lamp biomicroscope. CLD was assessed by the Ocular Surface Disease Index questionnaire at baseline, 1w, 1m, 3m, 6m after wearing, and another 6 months post stop wearing. Results: Clinical signs and CLD significantly increased in the 1st week (P < 0.05). The microvascular response and DCs activations reached their peak at the 1st month interval (P < 0.05). During CL wear, CLD was positively related to corneal staining (B = 0.238, P = 0.002), papillary conjunctivitis (B = 0.245, P < 0.001) and microvascular blood flow velocity (B = 0.353, P < 0.001). After discontinuance, only the DC activation was still higher at that of 6 months, while the other signs recovered. Conclusions: The 1st week of CL wear was the main period for the appearance of ocular surface clinical signs and the 1st month was the main period of activation of subclinical inflammation. Corneal staining and conjunctival microvascular response were the main factors affecting CLD. Even if the clinical signs had recovered after stopping wear, the sub-clinical inflammation might persist.